Altered serum amyloid beta and cerebral perfusion and their associations with cognitive function in patients with subcortical ischemic vascular disease - Zhang, Wei; Li, Mingxu; Zhou, Xia; Huang, Chaojuan; Wan, Ke; Li, Chenchen; Yin, Jiabin; Zhao, Wenming; Zhang, Cun; Zhu, Xiaoqun; Sun, Zhongwu (Frontiers in Neuroscience, 2022)
Subcortical ischemic vascular disease (SIVD) is one of the important causes of cognitive dysfunction, altered amyloid-beta (Aβ) and cerebral perfusion may be involved in the pathophysiological mechanism of SIVD and are closely related to cognitive function. We aimed to investigate altered serum Aβ and cerebral perfusion in patients with SIVD and their correlation with cognitive function. 74 healthy controls (HCs) and 74 SIVD patients, including 38 SIVD patients with no cognitive impairment (SIVD-NCI) and 36 SIVD patients with mild cognitive impairment (SIVD-MCI) underwent the measurement of serum Aβ40 and Aβ42 levels, pseudo-continuous arterial spin labeling MRI scanning, and cognitive evaluation. Compared to the healthy controls (HCs), the level of serum Aβ40 and Aβ40/42 ratio increased and Aβ42 decreased in SIVD patients. The serum Aβ40 level and Aβ40/42 ratio in patients with SIVD-MCI were significantly higher than those in the HCs and SIVD-NCI, and the level of Aβ42 in the SIVD-MCI was lower than the HCs. In addition, the serum Aβ40/42 ratio provided high diagnostic accuracy for SIVD and SIVD-MCI, it was further identified as an independent risk factor for cognitive impairment. Patients with SIVD-NCI and SIVD-MCI exhibited both increased and decreased cerebral blood flow (CBF) in regional. The Aβ40/42 ratio was associated with global CBF, while altered global and regional CBF was associated with cognitive deficits. In addition, white matter hyperintensities volume (WMHV) correlated with Aβ40/42 ratio, CBF, and cognition. The relationship between Aβ40/42 ratio and cognition was partially mediated by altered CBF. Based on these results, we conclude that the serum Aβ40/42 ratio may be a potential biomarker that can complement current methods for the prediction and diagnosis of cognitive impairment in SIVD patients. In addition, serum Aβ may play a role in cognitive function by regulating CBF, which provides new insights into the intervention, treatment, and prevention of cognitive impairment in SIVD.